Thermal energy storage behaviour of form-stable polyethylene glycol/MWCNT- based phase change materials - Yadav, Aman; Samykano, Mahendran; Pandey, A.K.; Kalidasan, B.; Kumar, R. Reji; Kadirgama, Kumaran; Sofiah, A.G.N.; Ngui, Wai Keng (EDP Sciences, 2024)
Organic phase change materials (OPCMs) possess a remarkable ability to absorb and release latent heat during phase transitions, making them very promising for storing solar energy. Nevertheless, the extensive use of these materials encounters substantial obstacles arising from intrinsic difficulties, such as limited heat conductivity and chemical stability concerns. The authors of this innovative work have successfully led the way in developing a state-of-the-art nano-enhanced organic phase change material (Ne-OPCM). This novel substance utilizes polyethylene glycol (PEG) as the primary phase transition material, which is smoothly incorporated into a network of polymethyl methacrylate (PMMA) to reduce obstacles caused by molecular size and improve chemical durability. In order to overcome the issue of poor thermal conductivity, the researchers selectively used multi-walled carbon nanotubes (MWCNT) as a conductive filler. This resulted in a significant increase in the thermal conductivity of PEG-1000. In an ongoing study, thermal characteristics of the developed (Ne-OPCM) composites are evaluated for different weight fractions of 0.3 %, 0.7 %, and 1.0 % of MWCNT. In addition to the morphology, thermal property, chemical stability, optical absorptivity and the latent heat of the developed PEG-PMMA/MWCNT (Ne-OPCM) composite are evaluated using FESEM, FT-IR, UV-Vis spectroscopy TGA and DSC instruments. The thermal conductivity of PEG-PMMA/MWCNT (Ne-OPCM) composite was improved by 87.64 % with a dispersion of 0.7 wt% of MWCNT. The DSC conducted highest latent heat and melting point of a PEG-PMMA/MWCNT (NePCM) composite are 139.66 J/g & 40.4 °C occurring at 0.7 wt% of MWCNT. Consequently, the developed (Ne-OPCM) composites have promising potential in practical solar energy storage applications at the temperature range of 35-40 °C.